2018
DOI: 10.1038/s41598-018-22189-w
|View full text |Cite
|
Sign up to set email alerts
|

Interaction between alcohol consumption and methylenetetrahydrofolate reductase polymorphisms in thyroid cancer risk: National Cancer Center cohort in Korea

Abstract: The effect of alcohol intake on thyroid cancer is unestablished, and its interaction effects with genetic susceptibility are unclear. In this case-control study, the relationship among alcohol intake, the methylenetetrahydrofolate reductase (MTHFR) gene, and thyroid cancer risk has been evaluated. In total, 642 cases and 642 controls of Korean origin were included, and the genetic variants C677T and A1298C of the MTHFR gene were analysed. The interactions between alcohol-consumption behaviour and genetic varia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…MTHFR variants may affect MTHFR enzyme activity. Studies have shown that individuals with the homozygous variant (TT) have 70% lower enzyme activity and those with the heterozygous variant (CT) have 35% lower enzyme activity compared to the wildtype (CC) genotype (6). The TT genotype is commonly linked with elevated Hcy levels through reduction in the activity of MTHFR (23).…”
Section: Genotype Nmentioning
confidence: 99%
See 1 more Smart Citation
“…MTHFR variants may affect MTHFR enzyme activity. Studies have shown that individuals with the homozygous variant (TT) have 70% lower enzyme activity and those with the heterozygous variant (CT) have 35% lower enzyme activity compared to the wildtype (CC) genotype (6). The TT genotype is commonly linked with elevated Hcy levels through reduction in the activity of MTHFR (23).…”
Section: Genotype Nmentioning
confidence: 99%
“…The presence of MTHFR variants may affect MTHFR enzyme activity. Studies have shown that individuals with the homozygous variant TT have 70% lower enzyme activity, and heterozygous variant CT carriers have 35% lower enzyme activity, compared to the wildtype CC genotype (6). The frequency of the MTHFR C677T gene mutation varies among different ethnic groups (7).…”
Section: Introductionmentioning
confidence: 99%